2022
DOI: 10.1021/acs.jpcc.2c04629
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Loading-Dependent Intrinsic Framework Flexibility on Adsorption in UiO-66

Abstract: The vast majority of molecular simulations of adsorption in porous materials make use of the assumption that the framework of the porous material may be held rigid without significantly impacting the accuracy of the computed adsorption isotherm. One reason for this approximation is that explicit inclusion of framework flexibility in adsorption simulations dramatically increases the computational cost of the simulation. Approximate methods for including framework flexibility have been developed that are computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 117 publications
1
11
0
Order By: Relevance
“…This approach allows for a less computationally demanding means of accessing the variation in channel environment, but it relies on the assumption that the presence of guest molecules has a negligible impact on the dynamic configurations of the MOF, which does not hold true for all MOFs. 26,27 These computational approaches to incorporate flexibility have shown that framework motion can have strong effects on guest molecule properties, 19,[34][35][36][37][38] such as adsorption [39][40][41] and diffusivity, 25,27,[42][43][44][45][46][47][48]57 in accordance with experiment. 20,47,[58][59][60][61][62][63][64][65] Yang et al 47 studied the diffusion of methane in UiO-66 using flexible force fields and observed a significant improvement in prediction over rigid force fields, although predictions were still lacking in quantitative and qualitative agreement with experiment.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…This approach allows for a less computationally demanding means of accessing the variation in channel environment, but it relies on the assumption that the presence of guest molecules has a negligible impact on the dynamic configurations of the MOF, which does not hold true for all MOFs. 26,27 These computational approaches to incorporate flexibility have shown that framework motion can have strong effects on guest molecule properties, 19,[34][35][36][37][38] such as adsorption [39][40][41] and diffusivity, 25,27,[42][43][44][45][46][47][48]57 in accordance with experiment. 20,47,[58][59][60][61][62][63][64][65] Yang et al 47 studied the diffusion of methane in UiO-66 using flexible force fields and observed a significant improvement in prediction over rigid force fields, although predictions were still lacking in quantitative and qualitative agreement with experiment.…”
Section: Introductionmentioning
confidence: 75%
“…33 The dynamics of linker rotation have been probed experimentally, both in empty MOFs and in the presence of guest molecules. [21][22][23][24][25] Framework motion can influence guest molecule behavior, and the adsorbed guest molecules can also affect framework motion and pore size, 23,26,27 including through 'gateopening' mechanisms where linkers experience steric effects that lead to larger pores and framework changes. MOF linker functionalization can alternately enhance or suppress linker dynamics, depending on the functional group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent simulation studies investigating the influence of guest molecule adsorption in the UiO-66 framework have highlighted the importance of considering framework flexibility to accurately reproduce experimental results. 30 These newly developed force fields are specifically designed to be compatible with the MB-pol data-driven many-body potential for water. [31][32][33][34] MB-pol has been shown to accurately predict the properties of water from the gas to the condensed phases.…”
Section: Introductionmentioning
confidence: 99%